2023
DOI: 10.1002/cam4.5608
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of changes to work patterns in multidisciplinary cancer team meetings due to the COVID‐19 pandemic: A national mixed‐method survey study

Abstract: Background: It is not well understood the overall changes that multidisciplinary teams (MDTs) have had to make in response to the COVID-19 pandemic, nor the impact that such changes, in addition to the other challenges faced by MDTs, have had on decision-making, communication, or participation in the context of MDT meetings specifically. Methods: This was a mixed method, prospective cross-sectional survey study taking place in the United Kingdom between September 2020 and August 2021. Results: The participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The number of studies at each stage of the screening process is shown in Fig 1 . Study designs of included studies were mostly observational cross-sectional studies (n = 15) [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Other study designs were retrospective review of records with a cross-sectional survey (n = 12) [5,[31][32][33][34][35][36][37][38][39][40][41], meeting observations with cross-sectional survey (n = 1) [42], mixedmethod design (n = 3) [43][44][45], embedded study design (n = 1) [46], randomized controlled trials (n = 2) [47,48], descriptive qualitative synthesis using free-text cross-sectional surveys (n = 1) [49], and an anthropological analysis (n = 1) [50]. A detailed summary of study characteristics is shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The number of studies at each stage of the screening process is shown in Fig 1 . Study designs of included studies were mostly observational cross-sectional studies (n = 15) [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Other study designs were retrospective review of records with a cross-sectional survey (n = 12) [5,[31][32][33][34][35][36][37][38][39][40][41], meeting observations with cross-sectional survey (n = 1) [42], mixedmethod design (n = 3) [43][44][45], embedded study design (n = 1) [46], randomized controlled trials (n = 2) [47,48], descriptive qualitative synthesis using free-text cross-sectional surveys (n = 1) [49], and an anthropological analysis (n = 1) [50]. A detailed summary of study characteristics is shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study was published in 1999 [5]. Most studies had populations from VMDTMs based in the United States of America (n = 10) [5,18,21,25,26,33,35,37,38,46], followed by the United Kingdom (n = 8) [7,17,22,23,43,44,47,48]. The distribution of these studies is described in the S5 File.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations